Quality of Primary Health Services during the COVID-19 Pandemic: A Literature Review - Azwar Azwar; Sudarman Sudarman; Samsualam Samsualam (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Primary health services are health services provided to the community at the first level by emphasizing promotive and preventive aspects. However, in carrying out their duties and functions, primary health services must improve because of the COVID-19 pandemic. The purpose of this study is to see how primary health care can maintain quality in the COVID-19 pandemic. The method used was Literature Review obtained from Science Direct, Elsevier, Pubmed and NCBI with vulnerability in 2020-2021 and obtained 7 articles that met the inclusion and exclusion criteria. The results showed that there are two forms of primary health care in maintaining quality during a pandemic, namely imposing new service patterns and utilizing telehealth. With the results of this study, it can be a reference for primary health services in Indonesia so that they are better able to maintain the quality of service during the COVID-19 pandemic.